2021
DOI: 10.1016/j.ijpam.2020.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Breaking bad news to children with chronic kidney disease

Abstract: Introduction Breaking bad ne ws to caregivers of children with (CKD) [I can’t comment in the box] Title says to breaking bad news to children but in here, breaking bad news to caregivers. Please clarify and edit accordingly. is an important role of nephrologists. In our practice there has been a thought about parental dissatisfaction from breaking bad news to CKD patients. Caregiver’s preferences on how to be told the bad news in CKD childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A recent study by Almaiman et al (2021) shows 86.3 percent of those who received bad news preferred it to be delivered in a simplified scientific manner, which corresponds to almost all respondents' (98.7%) preference for using appropriate language or 'layman' language when breaking bad news. This is parallel to a previous study done by Randall and Wearn (2005) that the respondents insist for the bad news communication to be done clearly.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A recent study by Almaiman et al (2021) shows 86.3 percent of those who received bad news preferred it to be delivered in a simplified scientific manner, which corresponds to almost all respondents' (98.7%) preference for using appropriate language or 'layman' language when breaking bad news. This is parallel to a previous study done by Randall and Wearn (2005) that the respondents insist for the bad news communication to be done clearly.…”
Section: Discussionmentioning
confidence: 94%
“…Because the bearers of the news are considerate of the preferences of the recipients, they adjust their delivery manner to meet those preferences. Almaiman et al (2021) found that the majority of caretakers of children with chronic kidney illness preferred to receive bad news when they were alone with the bearers of the news (58.2 percent). This demonstrates that people value a private setting in which to receive bad news.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have explored and created communication strategies. In terms of patient emotional improvement, strategies like SPIKES focus on the effect of empathy response ( Atienza-Carrasco et al, 2018 ; Toutin-Dias et al, 2018 ; Marschollek et al, 2019 ; Mirza et al, 2019 ; Almaiman et al, 2020 ; Rasmus et al, 2020 ; Bukowski et al, 2021 ). Apart from that, the information need ( Friedrichsen et al, 2000 ; Almyroudi et al, 2011 ) plays an important role in patient satisfaction and decision-making ( Friedrichsen et al, 2000 ; Almyroudi et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%